Canadian Association of Gastroenterology and the Canadian Digestive Health Foundation: Guidelines on Colon Cancer Screening. (1st February 2004) - Leddin, Desmond; Hunt, Richard; Champion, Malcolm; Cockeram, Alan; Flook, Nigel; Gould, Michael; Kim, Young-In; Love, Jonathan; Morgan, David; Natsheh, Susan; Sadowski, Dan; for the Canadian Association of Gastroenterology and the Canadian Digestive Health Foundation committee on colon cancer screening,
Abstract : Colorectal cancer is the third most prevalent cancer affecting both men and women in Canada. Many of these cancers are preventable, and the Canadian Association of Gastroenterology (CAG) and the Canadian Digestive Health Foundation (CDHF) strongly support the establishment of screening programs for colorectal cancer. These guidelines discuss a number of screening options, listing the advantages and disadvantages of each. Ultimately, the test that is used for screening should be determined by patient preference, current evidence and local resources.